2008
DOI: 10.1080/01902140701884406
|View full text |Cite
|
Sign up to set email alerts
|

Airway Inflammatory Responses to Oxidative Stress Induced by Prolonged Low-Dose Diesel Exhaust Particle Exposure From Birth Differ Between Mouse Balb/C and C57bl/6 Strains

Abstract: The authors used BALB/c and C57BL/6 mouse strains to search for genetically based differences in response to prolonged (6 months) low-dose (100 microg/m3) diesel exhaust particle (DEP) exposure from birth in terms of airway inflammatory responses. Histopathological assessment showed that inflammatory cells infiltrated the perivascular areas only in C57BL/6 mice. The count of DEP-laden alveolar macrophages in bronchoalveolar lavage (BAL) fluid was significantly greater in BALB/c mice (P < .05) than in C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(55 reference statements)
0
13
1
Order By: Relevance
“…It has been reported that exposure of mice to some environmental pollutants such as lead, residual oil fly ash (ROFA), and diesel exhaust particles at the prenatal, perinatal, or postnatal stage increases the level of IgE-or ovalbumin (OVA)-specific IgG1 antibody production (Snyder et al, 2000;Hamada et al, 2007;Li et al, 2008). In contrast to these studies, we found decreased total IgE in the present study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…It has been reported that exposure of mice to some environmental pollutants such as lead, residual oil fly ash (ROFA), and diesel exhaust particles at the prenatal, perinatal, or postnatal stage increases the level of IgE-or ovalbumin (OVA)-specific IgG1 antibody production (Snyder et al, 2000;Hamada et al, 2007;Li et al, 2008). In contrast to these studies, we found decreased total IgE in the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…We hypothesized that possibly the perinatal exposure to low-level toluene may increase systemic or local Th2-type responses and that the combination with PGN stimulation may suppress the enhanced Th2-type responses in infant mice. Exposure of fetuses or infant mice to some environmental pollutants increased the level of Th2-dependent IgE and IgG1 antibody production (Snyder et al, 2000;Hamada et al 2007;Li et al, 2008). Moreover, in our previous study, it has been demonstrated that interferon (IFN)-, a Th1-type cytokine, in bronchoaleolar lavage (BAL) fluid from adult mice was suppressed by low-level toluene exposure .…”
Section: Introductionmentioning
confidence: 96%
“…Susceptibility to the adverse effects of air pollutants is an intrinsic trait most probably related to genotypes [14]. Animal studies have shown that prolonged low-dose DEP exposure induces airway inflammatory responses that differ remarkably among mouse strains with different genetic backgrounds of oxidative stress response [15]. It has been proposed that host responses to DEP are regulated by a balance between antioxidant defenses and pro-inflammatory responses [16].…”
Section: Introductionmentioning
confidence: 99%
“…This could be mediated by one or more of a number of anti-oxidant enzymes [97,98]. Nrf2 is a redoxsensitive basic leucine zipper transcription factor that is involved in the transcriptional regulation of many anti-oxidant genes [99].…”
Section: Particulate Matter and Allergiesmentioning
confidence: 99%
“…These results strongly suggest that DEPs-induced oxidative stress and host antioxidant responses is regulated by Nrf2. The role played by Nrf2 in an allergic asthma model has been clearly demonstrated [100,101]; indeed, NAC treatment reduced the allergic inflammatory responses caused by DEP exposure [98]. Nrf2-/- mice exposed to low-dose DEPs exhibited significantly increased inflammatory cell numbers and periodic acid-Schiff staining-positive mucus cell hyperplasia.…”
Section: Particulate Matter and Allergiesmentioning
confidence: 99%